Influence of Germinated Brown Rice Production by Water Spraying Method on Its Qualities - Thatchapol Chungcharoen; Sansanee Sansiribhanb; Ronnachart Munsin; Ratiya Thuwapanichayanan; Arkom Palamanit; Phanphruek Sukkeaw; Kittisak Phetpan (My University, 2022)
This study was aimed to compare the production time (germination and drying process) and quality of germinated brown rice (GBR) obtained from the water spraying-based GBR production (Sprayed-GBR) system and the water soaking-based GBR production (Soaked-GBR) system. The results showed that the Sprayed-GBR, in the germination process, required 2.5 h for spraying in a water spraying step to obtain paddy with the moisture content of 30% (w.b.) and 26 h in an incubation step to obtain the 90% germination percentage. This led to a shorter germination time compared to the Soaked-GBR, which required a germination time of 50 h for a 90% germination percentage. After germination, the moisture content of the Sprayed-GBR was lower than that of the Soaked-GBR. This provided a shorter drying time in the Sprayed-GBR (27 min) drying process compared with the Soaked-GBR (33 min). For GBR qualities, the Sprayed-GBR could decrease the unpleasant odor problem by providing a smaller number of attached microorganisms after germination (Shade drying), leading to a significantly higher score in the odor and the overall acceptability than the Soaked-GBR. This indicated that the Sprayed-GBR got more consumer acceptance. Moreover, the head rice yield value of the Sprayed-GBR was not different from that of the Soaked-GBR. However, the Sprayed-GBR provided a significantly lower GABA content and a significantly higher percentage of fissured kernels than the Soaked-GBR.
Keywords: Brown rice; GABA and Rice Research